PTMAc-PEG-PTMAc hydrogel modified by RGDC and hyaluronic acid promotes neural stem cells' survival and differentiation in vitro. Issue 65 (22nd August 2017) - Yang, Ruirui; Xu, Caixia; Wang, Tao; Wang, Yuanqi; Wang, Jingnan; Quan, Daping; Deng, David Y. B.
Abstract : The enhancement of the biological properties of hydrogels by surface modifying with bioactive molecules is of great significance, especially for the treatment of central nervous system injury by combining engrafted cells. Abstract : The enhancement of the biological properties of hydrogels by surface modifying with bioactive molecules is of great significance, especially for the treatment of central nervous system injury by combining engrafted cells. This study aimed to develop a novel polyethylene glycol (PEG)-based hydrogel modified by Arg-Gly-Asp-Cys (RGDC) and hyaluronic acid (HA) as a carrier of neural stem cells (NSCs) for applications in central nervous system disorders. These novel gels were synthesized successfully and confirmed by GPC curve and 1 H NMR. The G′ increased with the increase in the contents of HA in the blends and the pore size of the hydrogels was detected by SEM. We evaluated the adhesion, survival, and differentiation of NSCs on hydrogels modified by different proportions of RGDC and HA in vitro . The number of NSCs adherent on a 30% RGDC hydrogel was significantly higher than the number of NSCs adherent on 10% and 20% RGDC hydrogels. However, only 74% of the NSCs were viable in the 30% RGDC hydrogel. To further improve the survival rate of the NSCs, different proportions of HA were added to the 30% RGDC hydrogel to create Gel-1 (HA 33%) and Gel-2 (HA 50%). We found that both gel formulations, particularly Gel-1, increased the survival and differentiation rates of NSCs compared to the 30% RGDC hydrogel. Furthermore, Gel-1 exhibited low toxicity to NSCs, zebrafish embryogenesis, as well as the liver and kidneys in rats with spinal cord injuries at 1, 4, and 8 weeks. We conclude that this novel hydrogel (Gel-1) has good biocompatibility and can promote NSCs survival and differentiation into neurons. It could be used as a promising biological scaffold to treat central nervous system disorders in the future.